Chemical regulation of cropping in mango - Randeep K R (Department of Pomology and floriculture, College of Horticulture, 2012)
The experiment on ‘Chemical regulation of cropping in mango’ was taken up at Department of Pomology and Floriculture, college of Horticulture, Vellanikkara during September 2008 to June 2010.